Unravelling the effect of two herbicide resistance mutations on acetolactate synthase kinetics and growth traits. (9th March 2020) - Zhao, Ning; Yan, Yanyan; Du, Long; Zhang, Xiaolin; Liu, Weitang; Wang, Jinxin
Abstract : The herbicide resistance mutations Pro-197-Tyr and Trp-574-Leu have contrary effects on both pyruvate substrate binding and maximum reaction velocity of acetolactate synthase, highly correlated with the cost of resistance. Abstract: Gene mutations conferring herbicide resistance are hypothesized to have negative pleiotropic effects on plant growth and fitness, which may in turn determine the evolutionary dynamics of herbicide resistance alleles. We used the widespread, annual, diploid grass weed Alopecurus aequalis as a model species to investigate the effect of two resistance mutations—the rare Pro-197-Tyr mutation and the most common mutation, Trp-574-Leu—on acetolactate synthase (ALS) functionality and plant growth. We characterized the enzyme kinetics of ALS from two purified A. aequalis populations, each homozygous for the resistance mutation 197-Tyr or 574-Leu, and assessed the pleiotropic effects of these mutations on plant growth. Both mutations reduced sensitivity of ALS to ALS-inhibiting herbicides without significant changes in extractable ALS activity. The 197-Tyr mutation slightly decreased the substrate affinity (corresponding to an increased K m for pyruvate) and maximum reaction velocity ( V max ) of ALS, whereas the 574-Leu mutation significantly increased these kinetics. Significant decrease or increase in plant growth associated, respectively, with the 197-Tyr and 574-Leu resistance mutations was highly correlated with their impact on ALS kinetics, suggesting more likely persistence of the 574-Leu mutation than the 197-Tyr mutation if herbicide application is discontinued.